Kurt Wallander’s Journey into Autumn: A Reading of Henning Mankell's The Fifth Woman - John Lingard (Scandinavian-Canadian Studies, 2007)
ABSTRACT: The last decade has been a golden age of detective fiction in the four Scandinavian countries: Sweden; Denmark; Norway; and Iceland. If Henning Mankell stands in the first rank of Nordic mystery writers, it is because he takes the type of book known in Sweden as a “deckare” and gives it the complexity of a superior novel. Mankell not only endows his now famous detective, Kurt Wallander, with a brooding depth of character, but places him in a strikingly realistic setting, and a three-dimensional social context subject to the forces of change. Like the novels of Fyodor Dostoevsky and Thomas Hardy, the Wallander series has a memorable balance of plot, character, and atmosphere. In an article in The New York Times Book Review, Marilyn Stasio provides a concise summation of Mankell’s strengths as a novelist: “Apart from his uncommon skill at devising dense, multilayered plots, Mankell’s forte is matching mood to setting and subject.”